(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
The ongoing development of socio-economic spheres in our republic, further improvement of the quality of personnel training in the system of higher and secondary specialized education; enhancing students’ inquisitiveness, creativity, thinking abilities, and speech culture in vocational training based on modern achievements in science and technology; purposeful and effective use of information and communication technologies in mastering the intricacies of professions; and developing students’ skills for independent work are among the most pressing issues of today